The Effect of Service Quality on Satisfaction and its Implications on Trust: (A Survey on Patients at RSGM Maranatha) - Amalia, Gema Nurqolbi; Jusuf, Eddy; Suryana, Popo (Pascasarjana Universitas Pasundan, 2023)
Hospital services are currently an absolute thing in marketing its services, various problems that occur in terms of service can be identified, even though the service products provided are not the focus of the problem, it needs to be considered because service is a parameter in selling services at hospitals. This study attempts to discuss the effect of service quality and trust on patient satisfaction at RSGM Maranatha Bandung City. The research method used in this research is descriptive and verification method. The population in this study were patients who used health services at RSGM Maranatha Bandung City. The number of samples used was 100 people based on slovin calculations. The data collection method used in this study was a questionnaire. Analysis of research data using Path Analysis with the help of the SPSS for Windows data analysis tool. The results of the study show that service quality variables affect patient trust and satisfaction. Patient satisfaction affects trust and patient satisfaction is able to mediate the effect of service quality on patient trust.